Circulating tumor cells (CTCs) and cytokeratin 19 (CK19) mRNA as prognostic factors in heavily pretreated patients with metastatic breast cancer. (2018) - Morales, S.; Velasco, A.; Gasol, A.; Córdoba, F.; Vidal, J.; Serrate, A.; Valls, J.; Samame, J.C.; Gisbert, R.; Moral, D.; Llombart-Cussac, A.; Salud, A.; et al.
Abstract: Introduction: Circulating tumor cell (CTC) count and cytokeratin 19 (CK19) mRNA expression have a prognostic value for patients with metastatic breast cancer (MBC), but their clinical utility remains controversial. We studied CTC count and CK19 mRNA expression in the peripheral blood samples from heavily pretreated patients with MBC and their correlations with prognosis and response to the subsequent line of therapy. Methods: This prospective observational study included 67 consecutive patients with MBC who were on progression to systemic therapy, and criteria for a new line of systemic treatment were proposed outside a clinical trial. CTC counts and CK19 mRNA expression were measured by the CellSearch ® and RT-PCR methods, respectively, before and after the first cycle of treatment. Progression-free survival (PFS) was defined as the time elapsed between the initiation of the treatment and either the date of clinical or radiological tumor progression or death from any cause or the last follow-up. Cox proportional hazards regression model was used to assess the univariate prognostic value of CTC and CK19 mRNA expression on PFS and Kaplan–Meier estimates. A multivariate Cox model was also used to additionally account for phenotype and visceral disease. Results: The mean age was 60 (range 35–86) years, and the average number of previous treatments was 3 (range 1–10); 42 patients (62.6%) were ER+ and 38 patients (56.7%) had visceral disease. The median PFS rate was 8 months (95% CI: 3.7–8.2). Univariate analyses showed a significant effect of the initial value of CK19 mRNA expression (HR = 2.00; 95% CI: 1.05–3.8; p = 0.03) and for the second value of CTC (HR = 2.18; 95% CI: 1.22–3.9; p = 0.009) but did not reach statistical significance for the initial value of CTC and the second value of CK19 mRNA expression. The estimated PFS rates at 6 and 12 months were 75% and 31% for patients with a low initial value of CK19 mRNA expression and 36% and 10% for those with a high initial value of CK19 mRNA expression, respectively ( p : 0.022). Further, the estimated PFS rates at 6 and 12 months were 86% and 65% for patients with a low second value of CTC and 76% and 47% for those with a high second value of CTC, respectively ( p : 0.004). In the multivariate analysis adjusted for phenotype, visceral disease, and the last treatment performed, only the effect of the second value of CTC remained significant (HR = 2.7, p = 0.004). Conclusions: CK19 mRNA expression and CTC count appeared clinically meaningful in pretreated patients with MBC, even when adjusted for phenotype and visceral disease involvement. These results support the use of CK19 and CTC as relevant biomarkers for predicting clinical response in MBC.